A HOLISTIC APPROACH TO EXTRA-JUDICIAL ENFORCEMENT AND PRIVATE DEBT COLLECTION - A Comparative Account of Trends, Empirical Evidences, and the Connected Regulatory Challenges - PART TWO - Tajti, Tibor (Pravni zapisi, 2020)
The article is a comparative account of empirical evidences and regulatory responses on the practices and corollary problems of private debt collectors as compared to private bailiffs and repossession agents. Part Two of this article is an overview of related contemporary laws. Anglo-Saxon systems (United Kingdom and the United States), as possessing the most developed regulatory systems. European civil law jurisdictions, where besides a brief account of Danish, French and Italian laws, the focus is on Germany in which its 2008 Act on Extra Judicial Legal Services is ongoing. Central and Eastern European (post-socialist) systems, all having reformed their bailiff systems, but having failed to face the challenged the appearance of private debt collectors on their markets, will be covered, from Lithuania and Poland, to Croatia and Serbia Part One of the article has reflected on the importance of extra-judicial enforcement, clarified the terminology, and illustrated the corollary problems through two brief case studies from Hungary. One on the activities of private car-repossession companies, and the other on the aggressive collection practices of private debt collectors. These were then assessed under sector-specific laws of Australia and the United States as developed regulatory systems. Key terms: extra-judicial (out-of-court) enforcement, self-help repossession, private debt collection, factoring (sale of receivables), hard and soft regulation, self-regulation, secured transactions, leasing, law reforms, comparative law.